2022
DOI: 10.1186/s12920-022-01180-5
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and atrial fibrillation: insights from a bidirectional Mendelian randomization study

Abstract: Background Observational studies have suggested that obstructive sleep apnea (OSA) is in relation to atrial fibrillation (AF); however, these studies might be confounded and whether the relationship is causal remains unclear. We conducted a bidirectional Mendelian randomization (MR) study to clarify the causal inference between OSA and AF. Methods Genetic instruments for OSA and AF were obtained from genome-wide association studies. The fixed-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
0
10
0
2
Order By: Relevance
“…On the basis of publicly available GWAS, summary-level data were acquired (Chen L. et al, 2022). Data on circulating metabolites provided by GWAS were carried out by the University of Oulu (Kettunen et al, 2016), and the data on depression provided by GWAS were primarily performed by the University of Edinburgh (Howard et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of publicly available GWAS, summary-level data were acquired (Chen L. et al, 2022). Data on circulating metabolites provided by GWAS were carried out by the University of Oulu (Kettunen et al, 2016), and the data on depression provided by GWAS were primarily performed by the University of Edinburgh (Howard et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the GWAS summary statistics, the effect estimates and corresponding standard errors (SE) of these SNPs of circulating metabolites and depression were acquired. The data for exposure (circulating metabolites) and outcome (depression) were harmonized, and palindromic SNPs were removed (Chen L. et al, 2022). Using simex package in R software and the formula…”
Section: Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Недавно опубликованная работа L. Chen и соавт. (2022), в которой использовались инструменты менделевского генетического анализа, также подтверждает причинно-следственные связи генетически предсказуемого ОАС с более высоким риском ФП [25]. Показательными являются данные группы G. Traaen и соавт.…”
Section: ассоциированность оас и фибрилляции предсердийunclassified
“…Recent studies have suggested that OSA promotes AF through structural and electrical atrial remodeling. 2 A recent meta-analysis showed that continuous positive airway pressure (CPAP) therapy reduces AF recurrence risk by 42% in patients with OSA. 3 However, whether CPAP can prevent AF or convert AF to normal sinus rhythm remains controversial.…”
Section: Introductionmentioning
confidence: 99%